THE CONTENT OF VITAMIN D2 IN BASIL SEEDS DURING SEED PRIMING WITH COMPOSITIONS OF METABOLICALLY ACTIVE COMPOUNDS - Osypchuk , R. P.; Kuchmenko, O. (НДУ ім. М. Гоголя, 2026)
Basil (Ocimum basilicum L.) is found all over the world and is increasingly used in the food, pharmaceutical, and cosmetic industries. However, the nutritional and functional properties of its seeds have been little studied. In the human body, vitamin D can be synthesized in the skin under the influence of ultraviolet radiation, followed by activation in the liver and kidneys to form the active form D3 - cholecalciferol. It can also be obtained from plant sources in the form of vitamin D2 (ergocalciferol). This vitamin performs a wide range of important functions, including optimizing mineralization processes in the body, inhibiting the proliferation of transformed cells, suppressing metastasis, inhibiting the activity of microorganisms, neutralizing reactive oxygen species, and participating in the maintenance of normal insulin secretion, among others. The aim of this study is to determine the content of vitamin D2 in basil seeds and in the aqueous extract from these seeds using a modified determination method, as well as to evaluate the obtained results for statistical reliability. As a result of the study, it was established that dry basil seeds have a significantly higher content of vitamin D2 compared to aqueous extracts from the same seeds. An effective agricultural approach to increasing the content of biologically active compounds in plant organisms is the pre-sowing treatment of seeds with various substances. As a result of the conducted studies, it was demonstrated that the most effective increase in vitamin D2 content in basil seeds was observed after pre-sowing treatment with combinations EPM (vitamin E + para-oxybenzoic acid + methionine) and EQ (vitamin E + ubiquinone-10). This may be related to the особенності of vitamin D2 biosynthesis in basil seeds and the influence of vitamin E, ubiquinone, para-oxybenzoic acid, and methionine on this process. By evaluating the correlation between relative frequencies and the frequencies of a normal distribution, it can be concluded that the method for determining vitamin D2 content in basil seeds using a modified colorimetric approach yields accurate results with low error. Determination of vitamin D2 content in basil seeds and in aqueous extracts from basil seeds across all groups indicates the absence of background absorption and a small relative error. These results may be useful in further studies of vitamin D2 content in plant organisms
Keywords: basil seeds, vitamin D2, determination method, relative frequencies, normal distribution frequencies, background absorption